In vitro maturation: a five-year experience - Rösner, Sabine; Eberhardt, Ingeborg; Beuter-Winkler, Petra; Toth, Bettina; Strowitzki, Thomas (Acta obstetricia et gynecologica Scandinavica, 2012)
Objective. Although some patients may benefit from reduced follicle-stimulating hormone (FSH) application, in-vitro maturation (IVM) belongs to the rare treatment options in assisted reproduction. We summarize our five-year IVM experience. Design. Retrospective, observational study. Setting. Reproductive Medicine, University Hospital. Sample. 115 patients with polycystic ovary syndrome (PCOS) as well as patients after ovarian hyperstimulation syndrome (OHSS) from February 2005 to December 2009. Material and Methods. Stimulation started between day 3-10 of the menstrual cycle and FSH dosage was 125IU/day over three days. Ovulation was induced on the third day of FSH injection or one day afterwards and oocyte retrieval was performed 33-38 hours later. Oocytes were cultivated for 24 hours in IVM medium. Fertilization was carried out one day after oocyte retrieval and embryo transfer two days afterwards. Main outcome measures. Pregnancy rates. Results. 115 patients were included and 215 oocyte retrievals (intracytoplasmic sperm injection: n=125, 59%; in vitro fertilization: n=73, 34.4%) with 177 embryo transfers performed. The main reasons for IVM were: PCOS (71.7%) and OHSS (15.0%). Mean number of oocytes was 8.9/oocyte retrieval with 5.9 (64%) becoming mature, 2.8 (45.1%) being fertilized and 2.1 transferred. Pregnancy rate per transfer was 15.3% (n=27) with 13 live births (7.3%), one intrauterine death (0.6%), four miscarriages (2.3%) and nine biochemical pregnancies (5.1%). In 61 cases, fertilized oocytes were frozen and 32 cryotransfers were performed, resulting in three pregnancies. Conclusions. Although the pregnancy rate was low, IVM is very convenient for patients due to low FSH dosages and few appointments at low cost.